2024
DOI: 10.1007/s12325-024-02796-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–Response Efficacy Modeling to Support Trofinetide Dosing in Individuals with Rett Syndrome

Mona Darwish,
Julie Passarell,
James M. Youakim
et al.

Abstract: Introduction Trofinetide was recently approved for the treatment of Rett syndrome (RTT) on the basis of the efficacy and safety findings of the phase 3 LAVENDER study, which used a body weight-based dosing regimen. Exposure–response (E–R) efficacy modeling was used to characterize relationships between trofinetide exposure measures (maximum drug concentration and area under the concentration–time curve for the dosing interval of 0–12 h [AUC 0–12 ]) and efficacy endpoints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Additionally, a study conducted by Neul et al showed that trofinetide exhibited a significant change compared to placebo in the communication ability measuring scales, the caregiver-rated Communication and Symbolic Behavior Scales Developmental Profile™ Infant–Toddler Checklist (CSBS-DP-IT) Social Composite score and the Rett syndrome clinician rating of ability to communicate choices (RTT-COMC) [ 21 ]. Furthermore, an exposure–response (E-R) efficacy model by Darwish et al [ 22 ] demonstrated that high trofinetide exposure improved the Rett Syndrome Behavior Questionnaire (RSBQ), CSBS-DP-IT, and RTT-COMC scores. Trofinetide was much better than placebo in reducing RSBQ total scores, with five to seven times greater reductions assuming target trofinetide with area under the concentration–time curve for the dosing interval 0 to 12 h (AUC 0–12 ) values of 800–1200 μg·h/mL [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a study conducted by Neul et al showed that trofinetide exhibited a significant change compared to placebo in the communication ability measuring scales, the caregiver-rated Communication and Symbolic Behavior Scales Developmental Profile™ Infant–Toddler Checklist (CSBS-DP-IT) Social Composite score and the Rett syndrome clinician rating of ability to communicate choices (RTT-COMC) [ 21 ]. Furthermore, an exposure–response (E-R) efficacy model by Darwish et al [ 22 ] demonstrated that high trofinetide exposure improved the Rett Syndrome Behavior Questionnaire (RSBQ), CSBS-DP-IT, and RTT-COMC scores. Trofinetide was much better than placebo in reducing RSBQ total scores, with five to seven times greater reductions assuming target trofinetide with area under the concentration–time curve for the dosing interval 0 to 12 h (AUC 0–12 ) values of 800–1200 μg·h/mL [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an exposure–response (E-R) efficacy model by Darwish et al [ 22 ] demonstrated that high trofinetide exposure improved the Rett Syndrome Behavior Questionnaire (RSBQ), CSBS-DP-IT, and RTT-COMC scores. Trofinetide was much better than placebo in reducing RSBQ total scores, with five to seven times greater reductions assuming target trofinetide with area under the concentration–time curve for the dosing interval 0 to 12 h (AUC 0–12 ) values of 800–1200 μg·h/mL [ 22 ]. LILAC study by Percy et al [ 23 ], a phase III open-label extension study of Neul et al study [ 20 ], assessed the safety and efficacy of trofinetide after 40 weeks of treatment in 154 females with RTT, aged 5–21 years.…”
Section: Introductionmentioning
confidence: 99%